A novel αB-crystallin R123W variant drives hypertrophic cardiomyopathy by promoting maladaptive calcium-dependent signal transduction - Chou, Chun; Martin, Gregory L.; Perera, Gayani; Awata, Junya; Larson, Amy; Blanton, Robert; Chin, Michael T. (Frontiers in Cardiovascular Medicine, 2023)
Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiovascular disorder affecting 1 in 500 people in the general population. Characterized by asymmetric left ventricular hypertrophy, cardiomyocyte disarray and cardiac fibrosis, HCM is a highly complex disease with heterogenous clinical presentation, onset and complication. While mutations in sarcomere genes can account for a substantial proportion of familial cases of HCM, 40%–50% of HCM patients do not carry such sarcomere variants and the causal mutations for their diseases remain elusive. Recently, we identified a novel variant of the alpha-crystallin B chain (CRYABR123W) in a pair of monozygotic twins who developed concordant HCM phenotypes that manifested over a nearly identical time course. Yet, how CRYABR123W promotes the HCM phenotype remains unclear. Here, we generated mice carrying the CryabR123W knock-in allele and demonstrated that hearts from these animals exhibit increased maximal elastance at young age but reduced diastolic function with aging. Upon transverse aortic constriction, mice carrying the CryabR123W allele developed pathogenic left ventricular hypertrophy with substantial cardiac fibrosis and progressively decreased ejection fraction. Crossing of mice with a Mybpc3 frame-shift model of HCM did not potentiate pathological hypertrophy in compound heterozygotes, indicating that the pathological mechanisms in the CryabR123W model are independent of the sarcomere. In contrast to another well-characterized CRYAB variant (R120G) which induced Desmin aggregation, no evidence of protein aggregation was observed in hearts expressing CRYABR123W despite its potent effect on driving cellular hypertrophy. Mechanistically, we uncovered an unexpected protein-protein interaction between CRYAB and calcineurin. Whereas CRYAB suppresses maladaptive calcium signaling in response to pressure-overload, the R123W mutation abolished this effect and instead drove pathologic NFAT activation. Thus, our data establish the CryabR123W allele as a novel genetic model of HCM and unveiled additional sarcomere-independent mechanisms of cardiac pathological hypertrophy.